Tumor Selectivity of Oncolytic Parvoviruses: From in vitro and Animal Models to Cancer Patients - Angelova, Assia L.; Geletneky, Karsten; Nüesch, Jürg P. F.; Rommelaere, Jean (Frontiers in Bioengineering and Biotechnology, 2015)
Oncolytic virotherapy of cancer is among the innovative modalities being under development and especially promising for targeting tumors which are resistant to conventional treatments. Presently, at least a dozen of viruses, belonging to nine different virus families, are being tested within the frames of various clinical studies in cancer patients. Continuously growing preclinical evidence showing that the autonomous rat protoparvovirus H-1 (H-1PV) is able to kill tumor cells that resist conventional treatments and to achieve a complete cure of various human tumors in animal models argues for its inclusion in the arsenal of oncolytic viruses with an especially promising bench to bedside translation potential. Oncolytic parvovirus safe administration to humans relies on the intrinsic preference of these agents for quickly proliferating, metabolically and biochemically disturbed tumor versus normal cells (tumor selectivity, or oncotropism). The present review summarizes and discusses (i) preclinical evidence of H-1PV innocuousness for normal cells and healthy tissues in vitro and in animals, respectively; (ii) toxicological assessments of H-1PV mono- or combined therapy in tumor-bearing virus-permissive animal models; as well as (iii) historical results of experimental infection of human cancer patients with H-1PV. Altogether, these data argue against a risk of H-1PV inducing significant toxic effects in human patients. This highly favorable safety profile allowed the translation of H-1PV preclinical research into a Phase I/IIa clinical trial being currently in progress.